The journalistic investigation competence education in students of Bachelor of Journalism - Cruz Fernández, Meilys; García Batán, Jorge (Transformación, 2024)
Objective: The research aims at devising a pedagogical model for the training of journalistic research in journalism students Methods: The author rely on the methods of analysis and synthesis, induction and deduction, the ascension of the abstract to the concrete, modeling and functional structural system, as well as the bibliographic review techniques and documentary analysis techniques. Result: The main finding is a theoretical construction that synthesizes contextualized knowledge for the journalistic research of social reality from the reflexive analysis of the context, critical thinking and ethical and comprehensive professional performance, which favors the autonomous, ideal and successful performance of the student of journalism in the investigation of social reality. Conclusions: The journalistic investigation competence training process should become part of the curriculum of journalist education. Consequently, the staff is expected to coordinate and plan a system of activities focus on promoting students’ active participation both in academic and practicum tasks under the guide of professor and tutors.